Focalization in Khaled Hosseini’s The Kite Runner - Rizky Rahman Mairizal Tanjung (Passage, 2017)
This research entitled Focalization in Khaled Hosseini’s The Kite Runner focuses on how focalization relates to the narrative and its effect towards the story. Employing Genette’s (1980) theory of narrative and focalization, the research finds that the two types of focalization, internal dan external, create different effects on the story. Two major effects of focalization make the story become more relatable and helps the story evoke the reader’s curiosity. These effects further emphasize the prominent issues found within the story. These findings have shown how focalization in the novel successfully invites the reader to feel sympathetic towards the human aspect portrayed in the story. It is expected that the research would give the insight into the use of focalization and its effect on the narrativeKeywords: Focalization, Narratology, Genette’s theory, focalizer